Peran Pendidikan Terhadap Pengangguran di Jawa Timur - Kinasih, Hera Ruth; Nurlaili, Eka Indah (Universitas Pahlawan Tuanku Tambusai, 2025)
Education serves as an asset for human resources, enhancing both formal qualifications and skill sets, hence facilitating employment opportunities due to elevated competitive value and contributing to a reduction in poverty rates. Poverty has emerged as a principal issue in Indonesia, attributable to various factors, including inadequate educational attainment. The analytical approach used in this study is the Systematic Literature Review (SLR). By using the Systematic Literature Review (SLR) paradigm approach to published journals, the results show that there are various factors that affect unemployment such as low levels of education and also low awareness of learning.